Chromatic Dispersion Compensation Effect Performance Enhancements Using FBG and EDFA-Wavelength Division Multiplexing Optical Transmission System - Mounia Chakkour; Otman Aghzout; Badiaa Ait Ahmed; Fahd Chaoui; Mounir El Yakhloufi (International Journal of Optics)
An optical transmission system using Fiber Bragg Grating (FBG) and Erbium Doped Fiber Amplifier (EDFA) with new proposed model has been analyzed to overcome chromatic dispersion and attenuation phenomena. To evaluate the transmission system performance of the received signals, a simple model of one channel transmission has been developed in the first step. Also, optical fiber length and attenuation coefficient parameters have been investigated in detail to deal with the optimized corresponding parameter values. Results show that the performance of the optimized design parameters is very efficient in terms of output power (dBm), noise figure (dB), gain (dB), and Q-Factor. The model of one channel developed previously has been adapted to a complex model of four optical channels multiplexing with different wavelengths. FBG and EDFA have been also added to WDM technology system to enhance the chromatic dispersion and the signal attenuation. Results show that the new model is more efficient in terms of Q-Factor and eye diagrams.